2020
DOI: 10.1088/1755-1315/441/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feed larvae Chironomus sp. and high pellet protein to seedling goldfish (Carassius auratus)

Abstract: Goldfish production increase in four years, specifically 66,823,000 in 2010 to 72,997,000 in 2014. The increment of goldfish production growth altogether with problems which is a discontinuity of fry stock. The solution for this problem is the purpose of this study, which is understood techniques in Goldfish (Carassius auratus) hatchery. The feed given to goldfish brood is blood worms (Chironomus sp. larvae) and pellets with a ratio of 50:50 as much as 3% of the biomass. Goldfish hatchery techniques involve br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Temperature is the same as salinity, having a positive relationship with an abundance of gastropods (Cabuk et al, 2004;Dwiardan et al, 2020;Damayanti et al, 2020). Garg et al (2009) revealed that high water temperature caused increased decomposition so that the amount of organic matter and macrophytes increased.…”
Section: Condition Of the Sedati Watersmentioning
confidence: 99%
“…Temperature is the same as salinity, having a positive relationship with an abundance of gastropods (Cabuk et al, 2004;Dwiardan et al, 2020;Damayanti et al, 2020). Garg et al (2009) revealed that high water temperature caused increased decomposition so that the amount of organic matter and macrophytes increased.…”
Section: Condition Of the Sedati Watersmentioning
confidence: 99%
“…If the water quality of the maintenance media is appropriate, it will support the cultivation of Daphnia magna. [29] states that cultivated organisms will eat as much feed as they get and will grow rapidly if the water quality is good and suitable for life, on the contrary if the water quality is poor, it will cause the cultured organisms to be stressed and disturbed so that their nutrient absorption will be reduced [30].…”
Section: Resultsmentioning
confidence: 99%
“…Maintenance techniques for Tilapia broodstock included pond preparation, broodstock preparation, broodstock selection, broodstock feeding, water quality management, and pest and disease control [13] [14]. Tilapia can be produced in different farming systems and scales with higher or lower dependence on inputs, especially feed.…”
Section: Maintenance Techniques For Tilapia Broodstockmentioning
confidence: 99%